Arginine inhibits cross-kingdom interactions and synergistic cariogenicity between Streptococcus mutans and Candida albicans - Gao, Hong-yu; Yang, Hao; Wang, Hong-mei; Li, Hao-ming; Ma, Yan-song; Bai, Yu-xing (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionStreptococcus mutans and Candida albicans are common pathogenic organisms from the oral microbial community, and are associated with the pathogenesis of caries. We investigated the repressive effects of arginine on the cross-kingdom interactions and synergistic cariogenicity between S. mutans and C. albicans.MethodsThe effect of arginine on the growth of S. mutans and C. albicans in the planktonic state was reflected by analyzing growth curves and pH measurements. Biofilm biomass was measured using growth curves, crystal violet staining, and colony-forming unit measurements; fluorescence in situ hybridization indicated the physical relationship between S. mutans and C. albicans in biofilms. The cariogenic properties of dual-species biofilms were analyzed through extracellular polysaccharide and lactic acid production assessments.ResultsArginine inhibited the planktonic growth and biofilm formation of S. mutans and C. albicans, with reduced biofilm formation, biomass, and physical adhesion between strains. Moreover, arginine suppressed the production of extracellular polysaccharides and lactic acid. In addition, short-term arginine treatment effectively inhibited the growth of S. mutans and C. albicans.ConclusionL-Arginine inhibited both mono- and dual-species growth of S. mutans and C. albicans. Thus, L-arginine may serve as a novel approach to inhibit the cross-kingdom interactions and synergistic cariogenicity of S. mutans and C. albicans.